Analysis Of Moral Messages In Mother Tongue Sign Language Films - Imandari, Indhira Resky; Dewi, Ambar Sari (LPPM Universitas PGRI Sumatera Barat, 2024)
The development of technology facilitates access to information, becoming a means to convey messages to many people. One of them is film, as a popular audio-visual media that is effective in presenting messages. Making films requires ideas, concepts, and a long time to produce quality work. Many films are made every year from various sources, with various functions such as education, entertainment, motivation, and others. However, it should be noted that films can also influence the moral values of society. The conclusion of the search for moral messages, researchers found the struggle of a mother to her deaf child. The struggle carried out by the mother was to learn sign language, then with love and patience tried hard to introduce it to her child who initially refused. But in the end the child was willing to learn sign language. With the provision of sign language that the child has, the world seems wide open, he can participate in various activities, both in the deaf community and in the hearing community, even the child can have achievements as a sign language interpreter.